Legends in sports: michael jordan eaudiobook - Christopher, Matt (Recorded Books Inc., 2012)
If you've ever wondered what it's like to be the best basketball player who ever lived, then Legends in Sports: Michael Jordan is the audiobook for you. In this exciting biography, Matt Christopher, the number one children's sportswriter in America, puts you on the basketball court with the legendary superstar. Take an inside look at the triumphs, struggles, and statistics of one of the most determined players in National Basketball Association history. By working hard and seizing opportunities, Michael Jordan became the unstoppable force that every team feared, and the most exciting player who ever lived.